Effect of intraoperative radiotherapy for patients with low-risk early-stage breast cancer - Diego Carreño; Camila Quirland; Pedro Ferrer; Luz María González; Badir Chahuán (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2021)
Introduction: External Beam Radiation Therapy (EBRT), a type of whole breast radiation therapy, has been widely used in patients with early-stage breast cancer, however it is associated with longer treatment periods and higher toxicity. Intraoperative Radiotherapy (IORT) has emerged as an alternative, reducing treatment times, however, there is uncertainty about its effectiveness and safety.  Objective: To assess the effects of IORT on low-risk early-stage breast cancer in comparison to EBRT.  Methods: We searched in Epistemonikos, a database of systematic reviews, to identify the available evidence evaluating the benefit of IORT on these patients. We extracted data of primary studies from relevant systematic reviews. Data were reanalyzed and a meta-analysis, using evidence of randomized trials, was conducted. Results are reported trough a summary of findings table using the GRADE approach.  Results and conclusions: We identified eight systematic reviews including seven primary studies overall, of which two were randomized trials. We concluded that IORT slightly reduces adverse events and probably increases the local recurrence rate in comparison with EBRT.